1993
DOI: 10.1099/0022-1317-74-6-1207
|View full text |Cite
|
Sign up to set email alerts
|

A genetically determined host factor controlling susceptibility to encephalomyocarditis virus-induced diabetes in mice

Abstract: Levels of insulin mRNA in pancreata from SJL/J male mice susceptible to encephalomyocarditis (EMC)-D virus-induced diabetes started to decrease rapidly 24 h after injection with EMC-D virus and only a trace remained 72 h after injection. In contrast, insulin mRNA in pancreata from C57BL/6J male mice resistant to EMC-D virus-induced diabetes did not show any significant changes 0 to 96 h after injection. EMC-D viral RNA in pancreata from SJL/J mice started to increase rapidly 24 h after injection, reached its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 28 publications
(43 reference statements)
1
23
0
Order By: Relevance
“…The data are consistent with the idea that EMC virus-induced diabetes follows Mendelian inheritance and that susceptibility is controlled by a single locus [78]. More recent experiments, in combination with earlier data, have indicated that a single gene controlling susceptibility to EMC-D virus-induced diabetes in mice can operate by modulating the expression of viral receptors on the beta cells [79].…”
Section: Control Of Emc Virus-induced Diabetes In Mice By the Viral Asupporting
confidence: 87%
“…The data are consistent with the idea that EMC virus-induced diabetes follows Mendelian inheritance and that susceptibility is controlled by a single locus [78]. More recent experiments, in combination with earlier data, have indicated that a single gene controlling susceptibility to EMC-D virus-induced diabetes in mice can operate by modulating the expression of viral receptors on the beta cells [79].…”
Section: Control Of Emc Virus-induced Diabetes In Mice By the Viral Asupporting
confidence: 87%
“…Infection of genetically susceptible mice with the M variant of EMC virus resulted in the selective destruction of pancreatic beta cells [132] (Figure 4). Further research found that beta cell destruction in EMC virus-infected mice is dependent on the genetic makeup of the virus and the genetic background of the host [133][134][135][136][137][138][139][140].…”
Section: Encephalomyocarditis Virusmentioning
confidence: 99%
“…As with other picornaviruses, it consists of 4 capsid proteins, 3 of which (VP1, VP2, and VP3) are exposed on the surface of the virion. Among the 3, VP1, the major outer capsid protein, is believed to play an important role for virus attachment and immunogenicity (31,32).…”
Section: Discussionmentioning
confidence: 99%